ELABORAÇÃO E IMPLANTAÇÃO DE PROTOCOLO DE PREVENÇÃO E MANEJO DE QUEDAS EM PEDIATRIA - Rebouças, Geisa Fonseca (2021)
Introduction: The proposal to develop and implement a specific institutional fall protocol for the pediatric population emerged from the author's experience as a quality leader in the pediatric sector, as from the institution's need to build and implement actions for the prevention and management of pediatric falls with the health professionals, answering a prerogative of the National Patient Safety Program, in order to mitigate risks and reduce the occurrence of this type of incident. Objectives: To describe the process of elaboration and implementation of a protocol for the prevention and management of falls in pediatrics. Methodology: Action research operationalized by the 12 phases of Thiollent's action research and grouped by the researcher into 3 action axes: 1. Preparation — literature review; preparation of the preliminary protocol and formation of the working group with 10 members of the multidisciplinary team; 2. Execution — restructuring and approval of the fall prevention and management protocol by the working group, by consensus, in two online rounds and three in-person seminars. The in-person seminars were recorded in a field diary, in mp3 format, later transcribed and analyzed using Bardin's content analysis technique; 3. Dissemination — reproduction of the information contained in the protocol to the hospital community and training of teams in loco, by work shift. Results/Product: The search for scientific evidence resulted in the preliminary version of the fall protocol, which was structured according to institutional reality and approved collectively by the working group during the seminars. Action research allowed the interaction between researcher and researched subjects, enabling convergence between formal and informal knowledge, theory and practice. In addition to the Pediatric Fall Prevention and Management Protocol, educational materials were produced for the family and health professionals (Orientation Poster; Orientation Leaflet; Identification Plate for Patients with High Risk of Falls; Flowchart of the prevention protocol and pediatric fall management). Conclusion: The protocol and educational materials are already in use at the institution and contribute to the management of the risk of falling in pediatric patients (0 to 18 years old) hospitalized, from the standardization of actions and conduct, adoption of preventive measures based on individualized risk assessment and the involvement of users, family members and professionals, in addition to making the results available to the scientific community. This research has the potential to generate impact and be applied at local, regional and national levels, as it systematically describes the steps and resources required for the elaboration and implementation of a Protocol for the Prevention and Management of Pediatric Falls.